Get Info. (Macaddict :a better machine, a better magazine.)
Apple wasn't the only company making waves at January's Mac Expo. There was also plenty of cool stuff released by both the big boys and mom 'n' pop shops. Plus, check out an iPod tube amp, the top tax software, the latest developments in the world of storage and a lot more.